MEMBERDAYAKAN âSTUDENTCENTEREDâ UNTUK MENGENAL âKATABENDAâ DALAM BAHASA INGGRIS - Adiana, Meilia (Jurnal Pengembangan Pendidikan, 2012)
Abstract. Language is a means of communications;it can be in spoken language, in a written text, in speech or inteaching-learning process. The language used in communication must be clear,well organized, and understandable.Â W.F.Bolton said: the ability to use language is the most distinctive characteristicof human beings and yet most people taken their language ability for granted,never considering its richness and complexity. It is also said by LudwigWittgenstein the limit of language means the limit of my world. In Englishthere is parts of speech consisting of noun, verb, adverb, adjective,conjunction, preposition, pronoun, and interjection. Taking one of them, thenoun, has many representations with the same name ânoun.â It is not so simpleto understand it. It needs some abilities to know it well. Almost students getlittle bit confused if they meet with noun in some representations. To know itbetter needs some ways, namely, reading a lot, rich of vocabulary, goodknowledge in English especially noun with its various representations. It hasthe same meaning but has many different representations. Student-centered is agood way to increase the studentâs ability to know ânounâ better.Â Â Keywords:parts of speech, noun, student centered.